Treatment by immunoadsorption for recurrent focal segmental glomerulosclerosis after paediatric kidney transplantation: a multicentre French cohort. Issue 6 (28th July 2017) - Allard, Lise; Kwon, Theresa; Krid, Saoussen; Bacchetta, Justine; Garnier, Arnaud; Novo, Robert; Deschenes, Georges; Salomon, Rémi; Roussey, Gwenaëlle; Allain-Launay, Emma
ABSTRACT: Background: Primary focal segmental glomerulosclerosis (FSGS) frequently recurs after kidney transplantation (KTx) in children. This can lead to delayed graft loss. As the management of children with recurrent FSGS is not well established, apheresis strategies could be a cornerstone to control the disease. Immunoadsorption (IA) is a recent apheresis therapy. There have been few studies examining IA in this setting. We report the results of IA for management of recurrent FSGS after KTx in children in France. Methods: We included all children treated with IA for early FSGS recurrence after KTx between January 2011 and June 2014 in France. We excluded genetic forms of FSGS. Patients' characteristics and technical data on IA were retrospectively collected. Recurrence was defined as nephrotic proteinuria during the post-transplantation period. Partial and complete remissions were defined when urine protein:creatinine ratios were less than 0.2 and 0.05 g/mmol, respectively. Results: Twelve patients, from six paediatric KTx units, presenting with FSGS recurrence between 0 and 21 days after KTx were treated with IA. Ten of 12 children were responders: 2 achieved partial remission and 8 complete remission. The decrease of proteinuria rapidly occurred within the first 10 sessions after initiating IA. After 3 months of IA, two patients maintained remission without IA and eight became IA dependent. No severe side effects were reported. Conclusions: Our study reports on the efficacy of IA in the recurrence of FSGS after KTx in children. Further prospective controlled studies are required to confirm these results and to optimize the management of FSGS recurrence after paediatric KTx.